Analisis Preferensi Konsumen terhadap Atribut Yogurt Drink (Studi Kasus Kota Bogor Jawa Barat) - Cahyanti, Tika; Najib, Mukhamad (Jurnal Aplikasi Manajemen, 2016)
Yoghurt is a dairy product that currently being developed. It can be proven by many options of yogurt product competes each other, therefore yoghurt producer has to know consumers'desires and needs. This study aims to identify the characteristics of consumer, identify buying decision process of consumer, analyze preferences and segmentation of consumer based on attribute importance weights. The research methods are using descriptive analysis, conjoint analysis, and cluster analyzes. The examined attributes are flavor,packaging, pricing, and volume/content of yoghurt. The result shows that flavor is the most important on yoghurt. While the most preferred combination by consumer is strawberry flavors, plastic bottle packaging, price Rp 7.000 - Rp 9.000 and volume 200-250 ml. The research resulted in two clusters based on attributes importance weights.